2020
DOI: 10.1097/md.0000000000021306
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of neutrophil-to-lymphocyte ratio in peripheral blood and pathological tissue in patients with esophageal squamous cell carcinoma

Abstract: The aim of this study was to investigate the prognostic value of neutrophils-to-lymphocyte ratio in peripheral blood (NLR) and in cancer nest (iNLR) in patients with esophageal squamous cell carcinoma (ESCC). Totally 103 patients with ESCC treated with surgical radical surgery in the Shuyang People's Hospital from February 2010 to November 2014 were collected retrospectively. Peripheral blood routine test and immunohistochemistry examination of carcinoma nest were mainly performed. Survival rates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…According to our results, NLR, SII and LMR showed prognostic value in the univariate analysis; however, only NLR remained an independent prognostic biomarker in the multivariate analysis. Recent studies have demonstrated that NLR may comprehensively reflect the inflammation and immune status of cancer patients ( 26 ), thereby representing a balance between the protumor inflammation and the anti-tumor immune status ( 27 ). The NLR indicates relative neutrophilia and lymphopenia, which has been related to shorter survival rates ( 11 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, NLR, SII and LMR showed prognostic value in the univariate analysis; however, only NLR remained an independent prognostic biomarker in the multivariate analysis. Recent studies have demonstrated that NLR may comprehensively reflect the inflammation and immune status of cancer patients ( 26 ), thereby representing a balance between the protumor inflammation and the anti-tumor immune status ( 27 ). The NLR indicates relative neutrophilia and lymphopenia, which has been related to shorter survival rates ( 11 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tissuelevel NLR needs to be further explored in a rigorous manner with validated and standardized techniques. Indeed, in a previous study, tissue-level NLR (assessed by immunohistochemistry for neutrophil-and lymphocyte-specific markers) in tumor nests, was shown to also predict clinical outcomes in patients with esophageal squamous cell carcinoma [5].…”
mentioning
confidence: 93%
“…In systemic inflammatory states, elevation of the ANC and depression of the ALC leads to elevation of the NLR. Several stud-ies have associated an elevated NLR with poor outcomes (overall and cancer-free survival, poor response to chemotherapy) in a variety of cancers including esophageal carcinoma [5,6]. While the exact mechanism of this phenomenon is unknown, inhibition of antitumor lymphocytes and natural killer cells by neutrophilic peritumoral inflammation is postulated [7].…”
mentioning
confidence: 99%
“…Although the well-established role of NLR in peripheral blood is known, the dynamics of this ratio in tissues are less explored. Its role was demonstrated in pancreatic cancer [15], esophageal squamous cell carcinoma [16], glioblastoma [17] and urothelial carcinoma [18], but not in melanoma.…”
Section: Introductionmentioning
confidence: 99%